Death and Immortality in Late Neoplatonism Studies on the Ancient Commentaries on Plato's Phaedo. - Gertz, Sebastian Ramon Philipp. (Studies in Platonism, Neoplatonism, and the Platonic Tradition, 2011)
The belief in the immortality of the soul has been described as one of the "twin pillars of Platonism" and is famously defended by Socrates in Plato's Phaedo . The ancient commentaries on the dialogue by Olympiodorus and Damascius offer a unique perspective on the reception of this belief in the Platonic tradition. Through a detailed discussion of topics such as suicide, the life of the philosopher and arguments for immortality, this study demonstrates the commentators' serious engagement with problems in Plato's text as well as the dialogue's importance to Neoplatonic ethics. The book will be of interest to students of Plato and the Platonic tradition, and to those working on ancient ethics and psychology.